Further insights from structural mass spectrometry into endocytosis adaptor protein assemblies - Heidemann, Johannes; Kölbel, Knut; Konijnenberg, Albert; Van Dyck, Jeroen; Garcia-Alai, Maria; Meijers, Rob; Sobott, Frank; Uetrecht, Charlotte (International journal of mass spectrometry, 2020)
As a fundament in many biologically relevant processes, endocytosis in its different guises has been arousing interest for decades and still does so. This is true for the actual transport and its initiation alike. In clathrin-mediated endocytosis, a comparatively well understood endocytic pathway, a set of adaptor proteins bind specific lipids in the plasma membrane, subsequently assemble and thus form a crucial bridge from clathrin to actin for the ongoing process. These adaptor proteins are highly interesting themselves and the subject of this manuscript. Using many of the instruments that are available now in the mass spectrometry toolbox, we added some facets to the picture of how these minimal assemblies may look, how they form, and what influences the structure. Especially, lipids in the adaptor protein complexes result in reduced charging of a normal sized complex due to their specific binding position. The results further support our structural model of a double ring structure with interfacial lipids. [Display omitted] •IM-MS and SID reveals that reduced charge states are a result of interfacial lipids.•ANTH subunits in the outer ring interact barely with each other and stabilize ENTH interaction.•Additional intermediates confirm our recent double ring model.